PENGARUH PROFITABILITAS, OPINI AUDITOR, DAN STRUKTUR KEPEMILIKAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Indah Suryani; Dahlia Pinem (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2018)
State revenue from the taxation sector remains dominating over This research is conducted to test the effect of variables Profitability, Audit Opinion, and Ownership Structure of the Timeliness of Financial Statement in the all companies Infrastructure, Utilities, and Transportation sectors listed in Indonesia Stock Exchange during 2013-2016. The population in this study amounted to 60 companies. Samples were obtained in this study amounted to 38 samples are selected by purposive sampling method. The analysis technique used here is logistic regression and hypothesis test using t-satistic with level of significance 5%. The results indicate that the variable Profitability not significant effect of the Timeliness of Financial Statement and variable Ownership Structure not significant effect of the Timeliness of Financial Statement. However, variable Audit Opinion significant effect of the Timeliness of Financial Statement